Blood conservation in arthroplasty - Gibbs, VN (2023)
Hip and knee arthroplasty are associated with significant blood loss which can exceed two litres, and 90% of patients are anaemic following arthroplasty surgery. Perioperative anaemia and allogeneic blood transfusion are associated with adverse outcomes. The aim of this thesis is to investigate strategies to minimise blood loss and perioperative anaemia in patients undergoing lower limb arthroplasty, offering improved patient outcomes and reduced healthcare costs.